L' Union politique de l'Europe : jalons et textes - Gerbet, Pierre; de La Serre, Françoise; Nafilyan, Gérard; Delors, Jacques (Paris : La Documentation française, 1998)
Bibliotheek François Vercammen
Frans
Monografie